Effects of selected animal blood and artificial diets on survival, growth, and chemical composition of Asian buffalo leech, Hirudinaria manillensis - Teh, Juan Chin (2012)
Hirudinaria manillensis is well-known as Asian medicinal leech which have been applied in traditional medicine and blood-letting therapy. H. manillensis which is also known as buffalo leech is a haemophagic fresh water leech that widely distributed in paddy field of Southeast Asia including Philippines, Southern China and Malaysia. This study investigated the effects of various casings as feed carriers (sheep intestine skin, cellulose sausage casings and rubber sacs), two different blood sources (cattle and poultry), feeding frequencies (once every 3, 6, 12, 24 days and no feeding), and some chemical compounds (sodium chloride, L-arginine, glycine,glucose) on growth, survival and body composition of Asian buffalo leech H.manillensis. Among the casings tested, the rubber sac has been found to be more suitable as a feed or blood carrier for H. manillensis. The leeches were able to detect the blood contained in the rubber sacs and successfully imbibed the blood. No blood leakage was observed after the leeches detached the sacs following completion of the feeding. The leeches fed with cattle blood had a significantly higher weight gain (88%) than poultry blood fed ones (39%). FCR was more efficient with cattle blood (2.57) compared to that of the poultry blood (4.19). However, no significant difference (P>0.05) was found on survival and body composition of the leeches fed on either blood. The leeches fed every 3 days had the highest growth (116%) followed by those fed every 12 days (92%), every 6 days (87%) and every 24 days (13%). However, there was no significant difference (P>0.05) among the growth of leeches that were fed every 3, 6 or 12 days. Therefore, a feeding regime of every 6 to 12 days interval was recommended for the culture of the leech H. manillensis as it was more cost effective from management view. A solution containing a combination of sodium chloride (150 mM), L-arginine (1 mM), glycine (50 mM) and glucose (1 mg/ml) invoked a feeding approach and food consumption similar to that of the cattle blood. Mortalities up to 40% were observed among all feeding leeches while survivals of the non-feeding leeches were always close to 100%. Overfeeding might be one of the reasons for this problem but a further research has to be carried out to find out the actual cause(s) of such heavy deaths among the feeding leeches.